Microstructure and mechanical properties of Mg-14Li-1Al-0.3La alloys produced by two-pass extrusion - Li, Ruihong; Jiang, Bin; Chen, Zhijun; Pan, Fusheng; Gao, Zhanyong (Journal of rare earths, 2017)
The microstructure of as-cast and extruded Mg-14 Li-1 Al-（0, 0.3） La alloys was examined with XRD,OM, SEM, and EDS. The mechanical properties of the extruded specimens with and without La were compared. The results show that La addition has an obvious effect on the microstructure of the as-cast LA141 alloy by reducing the average grain size from 600 to 220 μm. β-Li and LiMgAl2 phases are observed in both alloys, and long-rod-shaped Al2 La phase is also observed in the La containing alloy. After extrusion, Al2 La phases are short-rod-shaped and distribute evenly in the alloy. LAl41-0.3 La alloy has higher elongation（34%）, which is attributed to refined microstructure and weak texture due to shortrod-like Al2 La phase.